54‐1: Invited Paper: Development of Electroluminescent QD‐LED Displays. Issue 1 (29th May 2019) - Smeeton, Tim M.; Angioni, Enrico; Boardman, Edward A.; Izumi, Makoto; Iwata, Noboru; Nakanishi, Yohei; Ishida, Takeshi
Abstract : This paper reports on the potential of electroluminescent quantum dot LED (QD‐LED) as a future display technology and on the advances required to realise this potential. We give an example of progress in development of a UV lithography‐based fabrication process for QD‐LED devices.